Gathering Information for The Kuranty and Translation Technique at the Collegium of Foreign Affairs in the 1720s - Ingrid Maier; Stepan M. Shamin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
This paper deals with the Kuranty (digests of foreign newspapers) during the 1720s. The authors’ main focus is on the work of translators of the Collegium of Foreign Affairs on selection of materials for translation out of the newspapers sent to the Collegium by regular mail. The translation technique used for translating the foreign newspapers has also been analyzed. One of the conclusions consists in the fact that before translating newspapers, translators made notes in original texts thus marking the fragments necessary for translation, then they translated those fragments and passed the texts for reviewing to the heads of the Collegium of Foreign Affairs, who decided, which of the translated articles had to be presented to the Russian diplomats. During the 1720s, in contrast to the practice adopted in the 17th century, the Kuranty was a tool for not only learning about foreign events, but also for keeping the European newspapers under observation. A comparison of the translation techniques applied for the “old” and the “new” Kuranty shows that these techniques had not changed a lot since the 1670s: in both cases the translators put aside irrelevant information. For instance, they left out entire sentences, if they were of low importance for the Russian officials, and so forth. Talking about the newspaper articles, which have been compared with their German originals, they may be characterized as more accurate than the Kuranty of the 1670s – almost every single word of the original German text had an equivalent in the translation. Generally speaking, the professional level of the translators – which was quite high already in the 1660s–1670s – had improved still more during the reign of Peter I.